Diseño, elaboración y aplicación de un módulo en Sistema Braille para el aprendizaje de Inglés - Malca Monzon, Marco Antonio (2019)
Nowadays, visually impaired people have the right to education and all that it involves. However, in terms of foreign languages learning, not much has been done to promote the teaching of English to blind people in our town. The purpose of this project is to improve and encourage English language learning in visually impaired students of “Luis Braille – Blind Regional Association in La Libertad, Peru”, by means of the design, development and application of a module in Braille System. In order to get results, learning sessions were held, and an evaluation form was used as a data collection instrument for the four language skills: listening, reading, speaking and writing. For the analysis of results, the application - descriptive method with statistical graphs was used, which allowed us to know about the process of English Language Learning in visually impaired people by using the module called “Unlimited English for Blind Students” in Braille System. It was concluded that the application of the module significantly improves the learning of English in blind students.